Research Protocol to Evaluate the Effects of Alcohol Policy Changes in Lithuania. (27th September 2018) - Rehm, J; Štelemėkas, M; Badaras, R
Abstract : The staggered implementation of key alcohol policies in Lithuania over the past two years offers the possibility to evaluate 'best buys' for alcohol policies for this country. Lithuania is the only country where all 'best buys' were implemented over a short period of time, so this evaluation will be unique. Abstract: Aims: To point out the importance for public health to evaluate the past policy changes (2016–2018) in Lithuania. To present a research protocol to conduct this evaluation. Short summary: The staggered implementation of key alcohol policies in Lithuania over the past two years offers the possibility to evaluate 'best buys' for alcohol policies for this country. Lithuania is the only country where all 'best buys' were implemented over a short period of time, so this evaluation will be unique. Methods: Quasi-experimental design based on interrupted time-series analysis of monthly routine statistics of morbidity and mortality indicators as well as key variables on the pathway between alcohol exposure and health outcomes. Conclusions: For the public health community, results of the evaluation of these policy changes will be of critical importance.